2020
DOI: 10.1016/j.esd.2020.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking electric cooking on Nepali micro-hydropower mini-grids

Abstract: Electric cooking has the potential to improve quality of life for people who cook using biomass, both by improving health by eradicating harmful emissions and by removing the need to collect fuelwood, thus freeing up time for other activities. This paper reports on a study that introduced electric cooking as an alternative to biomass-based cooking in 10 households in Simli, a rural Western Nepali community, to assess its feasibility in rural offgrid contexts. Quantitative and qualitative data from a cooking di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…This will increase the use of direct electricity, especially in cooking [85]. Therefore, enhancing the quality of life of women and children mostly in rural areas by reducing time spent on collection of fuelwood thus creating additional opportunities for employment, heath improvement and education [86]. During the transition, the energy supply mix changes considerably from fuelwood and hydropower dominated electricity generation to solar PV electricity dominated in 2050.…”
Section: A Overall Resultsmentioning
confidence: 99%
“…This will increase the use of direct electricity, especially in cooking [85]. Therefore, enhancing the quality of life of women and children mostly in rural areas by reducing time spent on collection of fuelwood thus creating additional opportunities for employment, heath improvement and education [86]. During the transition, the energy supply mix changes considerably from fuelwood and hydropower dominated electricity generation to solar PV electricity dominated in 2050.…”
Section: A Overall Resultsmentioning
confidence: 99%
“…The scope of the appliances in question diverges from previous studies, and the present trial also differs in that the customers were trialing induction hobs rather than EPCs. In Clements et al [13], 10 households used induction stoves on a 30 kW MHP mini-grid in western Nepal. The authors used a version of the cooking diary methodology employed in this research to gather detailed data about stove use, fuel use, and cooking practices during a two-week baseline phase and a two-week electric cooking phase.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As well as powering households in a community, MHPs provide energy for commercial connections such as shops and mobile phone masts, community services including schools and health posts, and industrial end uses such as flour and grain mills, all of which can be referred to as productive end uses (PEUs) [3,[10][11][12][13]. MHPs are operated at constant power but community electricity demand varies widely, often from a relatively low level at off-peak times to a high level at peak times in the morning and evening [14,15]. Consequently, many MHPs suffer from low load factors and a large proportion of generated energy is wasted [5,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, rice cookers and electric kettles are becoming increasingly prevalent, comprising a significant proportion of demand due to their high power, and therefore increasing generated income where consumption is metered [10]. Recent electric cooking trial studies conducted by the authors in rural Nepal used cooking diaries to characterise the Nepali cooking context, collecting detailed information on participants' usage of traditional and electric stoves [14,15,22]. The studies found that, as people tend to cook at similar times and peak loads are often already high, with only 10 and 15 households cooking with electricity out of around 450 and 1100 households, respectively, the generation capacity was often reached, showing that electric cooking scalability in MHP communities is currently limited.…”
Section: Introductionmentioning
confidence: 99%